An update on the ocular manifestations of dengue - Christina Wang; Arturo Castillo; Federico Cortes-Bejarano; Eduardo Lopez; Eduardo Cunha de Souza; Lihteh Wu (Taiwan Journal of Ophthalmology)
Dengue is the most common arboviral disease. It is typically spread by the bite of an infected female Aedes aegypti or Aedes albopictus mosquitoes. Dengue is endemic in subtropical and tropical regions, but its geographic reach keeps expanding. Ophthalmic manifestations of dengue are common and may present with a wide spectrum of ophthalmic findings. These may range from conjunctival petechiae, retinal hemorrhage, retinal vasculitis to panophthalmitis. Some of these may be vision threatening and may require urgent ophthalmic evaluation. The precise pathophysiologic mechanisms involved in dengue infection involve a complex interplay between host immune responses, virus, and host genes. There is no specific treatment for ocular dengue. Therefore, treatment is supportive. Despite the lack of proven efficacy, corticosteroids have been used in vision-threatening dengue-related ocular complications. Dengue must be considered in endemic areas, and a careful travel history needs to be elicited in nonendemic areas.